Simpler UNBabc Mapping Function for Global Positioning System (GPS) Tropospheric Delay - Sakidin, Hamzah; Tay, Choo Chuan (2010)
The UNBabc(E) mapping function models should be simplified to allow faster calculation and also better understanding of the models. Many modern mapping function models use mapping functions in the form of continued fractions which is quite tedious in calculation. There are 11 mathematical operations for UNBabc(E) to be carried out before getting the mapping function scale factor. The mapping functions for UNBabc(E) models for hydrostatic and non hydrostatic components are given in a form of continued fraction are to be simplified. UNBabc(E) mapping function models are selected due to its ability to calculate mapping function value down to 2 degree of elevation angle. By using linear, hyperbolic, logarithm and also regression method, the mapping function models can be simplified and at the same time can produce the same result. The calculation of sum of errors shows that the deviation of the simplified models from the original models is not significant. The computation time between the original model and simplified model shows that the simplified UNBabc(E) model is 6.5 times faster than the original model for both hydrostatic and non hydrostatic component. As the coefficient of zenith hydrostatic delay and also zenith non hydrostatic delay, the mapping function scale factor value plays an important role for getting the total tropospheric delay value.